2017
DOI: 10.1016/j.str.2017.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Plant Multidrug and Toxic Compound Extrusion Family Protein

Abstract: The multidrug and toxic compound extrusion (MATE) family of proteins consists of transporters responsible for multidrug resistance in prokaryotes. In plants, a number of MATE proteins were identified by recent genomic and functional studies, which imply that the proteins have substrate-specific transport functions instead of multidrug extrusion. The three-dimensional structure of eukaryotic MATE proteins, including those of plants, has not been reported, preventing a better understanding of the molecular mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 44 publications
4
32
1
Order By: Relevance
“…Thus, the central cleft between the N-and C-lobes is closed on the intracellular side. These structural features of VcmN are also observed in other previously reported MATE transporter structures (Miyauchi et al, 2017;Tanaka et al, 2013Tanaka et al, , 2017He et al, 2010;Lu et al, 2013aLu et al, , 2013bMousa et al, 2016;Radchenko et al, 2015).…”
Section: Overall Structures Of Vcmnsupporting
confidence: 86%
See 1 more Smart Citation
“…Thus, the central cleft between the N-and C-lobes is closed on the intracellular side. These structural features of VcmN are also observed in other previously reported MATE transporter structures (Miyauchi et al, 2017;Tanaka et al, 2013Tanaka et al, , 2017He et al, 2010;Lu et al, 2013aLu et al, , 2013bMousa et al, 2016;Radchenko et al, 2015).…”
Section: Overall Structures Of Vcmnsupporting
confidence: 86%
“…the NorM, DinF, and eukaryotic subfamilies (Omote et al, 2006). Over the last decade, structural and biochemical analyses of MATE transporters have been intensively pursued (Miyauchi et al, 2017;Tanaka et al, 2013Tanaka et al, , 2017He et al, 2010;Lu et al, 2013aLu et al, , 2013bMousa et al, 2016;Radchenko et al, 2015). To date, the crystal structures of five prokaryotic MATE transporters have been reported: Vibrio cholerae NorM subfamily (NorM-VC) (He et al, 2010) simultaneously coupled to the Na + and H + gradients (Jin et al, 2014), two Na + -driven MATE transporters (Neisseria gonorrhoeae NorM [NorM-NG] [Lu et al, 2013a] and Escherichia coli DinF subfamilies [ClbM] [Mousa et al, 2016]), and two H + -driven MATE transporters (Pyrococcus furiosus DinF [PfMATE] and Bacillus halodurans DinF subfamilies [DinF-BH] [Lu et al, 2013b;Radchenko et al, 2015]).…”
Section: Introductionmentioning
confidence: 99%
“…Based on their amino acid sequence similarity, the MATE family members are classified into the NorM, the DNA damage-inducible protein F (DinF), and the eukaryotic subfamilies (2). In recent years, the crystal structures of representative members of all three subfamilies have been published (7)(8)(9)(10)(11)(12)(13)(14)(15). Since all of them represent only an outward-facing state, a detailed understanding of the complete transport cycle has remained elusive.…”
mentioning
confidence: 99%
“…Until very recently, the canon of MATE structures was limited to outward-facing (OF) conformations in which the two lobes, related by an intramolecular two-fold symmetry and connected by a cytoplasmic loop, diverge and orient away from each other near the middle of the membrane forming a large central cavity open to the extracellular side [16][17][18][19][20][21][22][23] . Crystal structures of a NorM transporter from N. gonorrheae, NorM-Ng, bound to tetraphenylphosphonium, ethidium, and rhodamine 6G (R6G) demonstrated that substrates can bind to the same location within the central cavity between the two lobes 18 .…”
mentioning
confidence: 99%